PS-R04-3: A CASE OF RESISTANT HYPERTENSION. (January 2023) - Nakajima, Yuya; Irie, Junichiro; Nakamura, Toshifumi; Kawano, Yoshinaga; Ito, Arata; Kinouchi, Kenichiro; Kobayashi, Sakiko; Meguro, Shu; Itoh, Hiroshi
Abstract : Background: Resistant hypertension is defined as blood pressure that remains above 140/90 mmHg despite the use of three antihypertensive medications of different classes at the maximally tolerated doses, one of which is a diuretic. It is reported that approximately 10% of patients with hypertension have resistant hypertension, but the optimal management of resistant hypertension remains to be unclear. Case presentation: A 56-year-old Japanese woman visited our hospital because she presented high blood pressure of about 170/100 mm Hg even after the treatment by her primary physician. She had hypertension after giving birth at age 26 and her blood pressure was about 170/100 mm Hg. She was suspected of having secondary hypertension and the laboratory and imaging examination were conducted. The functions of the adrenal gland and thyroid were normal, and the renal artery stenosis and chronic kidney disease were excluded. She did not have NSAIDs, oral contraceptives, and herbal products. Although she had been intensively treated for hypertension, she suffered from a brain hemorrhage. Her systolic blood pressure has been still not controlled appropriately by 80 mg of nifedipine, 400 mg of the combination of sacubitril/valsartan, 2.5 mg of esaxerenone, 2 mg of trichlormethiazide, and 9 mg of bisoprolol transdermal patch daily. Conclusion: Because patients with resistant hypertension have a higher risk of stroke, kidney disease, and heart failure, the careful examination and intensive treatment are necessary.